Synthesis and structural consideration of Metal-Organic Framework (MOF) coordination polymer with various metal linker ratios - Misran H. (Trans Tech Publications Ltd, 2023)
Metal-organic framework MOF-5 (i.e. IRMOF-1) with the chemical structure of Zn4O(BDC)3 were successfully synthesized using room temperature synthesis approach of direct-mixing method ans liquid-crystal templating method. The metal clusters organic linker used was benzenedicarboxylic acid (BDC). Direct-mixing approach resulted in MOF-5 with tetragonal cell while the liquid-crystal templating method resulted in cubic structure. The metal/linker ratios were varied from 0.1 to 1 to study the effect of metal linker on the formation of MOF-5 materials and their characteristics. The crystallinity of the evacuated framework MOF-5 materials were increased when the metal/organic linker ratios were increased from 0.3 to 0.5. However, the cubic structure of the evacuated framework was relatively disrupted at metal/linker ratio 0.7. (2011) Trans Tech Publications.